Innovations for a sustainable future: rising to the challenge of nitrogen greenhouse gas management in Latin America - Bustamante, Mercedes M. C. (2014)
Latin America encompasses a dizzying array of ecosystems and socioeconomic models, and the region will be highly vulnerable to the projected impacts of climate change in the next century. At the same time, Latin America can significantly contribute to the mitigation of greenhouse gases (GHG) emissions within a sustainable development framework. Land use conversion with associated biomass burning, agriculture with N fertilizers and animal waste are the main anthropogenic sources of nitrous oxide (N2O) emissions in the region, and have increased markedly in the last decades. Effective sustainable managementforthe mitigation of N2O emissions requires the proper evaluation of all sources, many of which are still roughly estimated or unknown, testing alternatives to reduce primary sources, and technological innovation for higher resource-use efficiency within the farm. Current barriers might be overcome through policies that support sustainable practices thatreduce negative environmental impacts and simultaneously maintaining ecosystem function and services.